Incorporación de hidrolizado de pulmón bovino, como aditivo antioxidante, en hamburguesas de pollo. - Martinez, Fernanda Gabriela (2024)
Today, consumers prefer foods with clean labeling, that is, that do not contain additives, or if they do, that they are of natural origin. This has caused the food industry to gradually replace artificial antioxidants with natural ones. In this sense, the peptides obtained from of animal by-products have antioxidant capacity, and for this reason They have potential use as an additive. The objective of this work was to evaluate the antioxidant capacity of a bovine lung hydrolyzate (BPH) in chicken burgers (model system) and compare its effect in relation to an antioxidant of synthetic origin such as BHT (butylhydroxytoluene). For this, the hamburgers with the following formulation: chicken breast, 80.9% (w/w); chicken skin, 8% (w/w); water, 8% (w/w), NaCl 1%, sunflower oil 2% (w/w), and additives antioxidants: BHT or HPB. The concentrations used of the additives antioxidants were: BHT 0.01% (BHT); HPB 0.025% (HPBB); HPB 0.05% (HPB); and HPB 0.025%/BHT 0.005% (HPB/BHT); and a control, without antioxidants. The oxidative progress of fresh chicken burgers was evaluated using the TBA and total antioxidant capacity by FRAP at 0, 3, 7 and 10 days of storage 4 °C in aerobiosis. In addition, the parameters were evaluated technological: weight loss by cooking, expressible humidity, pH, resistance to cut (Kramer cell) and chromatic parameters, both in raw and cooked – on a double contact grill at 165-180 °C (75 °C in the center). Regarding the evaluation of oxidative progress, no significant differences were observed (p>0.05) in the FRAP values ​​between the formulations and the control. However, for the TBA index, the formulations with the incorporation of HPB - HPBA and HPBB (0.9 ± 0.3 mg MDA/kg), were more stable than the control formulation (maximum recorded value 1.7 ± 0.5 mg MDA/kg). The most stable formulation was obtained with the addition of HPB/BHT, whose TBA index value remained constant (0.4 ± 0.2 mg MDA/kg) during the 10 days of storage. Regarding the parameters technological differences were not observed (p>0.05) between the different formulations and the control. The color parameters L* and b* in hamburgers raw chicken presented significant differences (p<0.05); however, after cooking these differences were not observed. In conclusion, bovine lung hydrolyzate with antioxidant capacity incorporated as an additive in beef hamburgers chicken delayed oxidation, and in combination with a synthetic antioxidant reduced its concentration by half, reaching maximum oxidative stability. The present work shows the potential of food additives derived from by-products and the development of new additives of natural origin for their application in the industry food.